EMPLOYEE ENGAGEMENT AS A MEDIATOR INFLUENCES OF WORK STRESS AND CAREER DEVELOPMENT TO TURNOVER INTENTION IN EMPLOYEE OFFICE OF PT PKSS CENTRAL OFFICE - Bawono, Wahyu; Singmin Johannes Lo (Dinasti International Journal of Management Science, 2020)
The objectives of this study are: (1) To analyze the Effect of Job Stress, Career Development and Job Satisfaction on Turnover Intention in PT PKSS and (2) To analyze the significant influence between Job Stress, Career Development and Employee Engagement simultaneously / Jointly towards Turnover Intention at PT PKSS. This research uses a quantitative method with a sample of all employees at PT PKSS, amounting to 98 people. The analysis technique used is Part Least Square Analysis (PLS). While the variables in this study are: (1) job stress, (2) career development, (3) employee engagement, and (4) turnover intention. The results of this study include: (1) Job stress has a significant effect on employee engagement with a T-Statistic value of 5,481, (2) Career development has a significant effect on employee engagement with a T-Statistic value of 4,909, (3) Work stress has a significant effect on turnover intention with a T-value Statistics of 3.071, (4) Career development has a significant effect on turnover intention with a T-Statistic value of 5.526, and (5) Employee employee variable can mediate jointly from the effect of work stress and career development on turnover intention. Can be proven by the analysis of VAF (Variance Accounted For) value calculation above, it can prove hypothesis 8 that employee engagement variable (Y1) can mediate the effect of work stress variables and career development together on turnover intention of 21.15%.